2022
DOI: 10.1093/ajcn/nqac131
|View full text |Cite
|
Sign up to set email alerts
|

Lipid emulsion rich in n–3 polyunsaturated fatty acids elicits a pro-resolution lipid mediator profile in mouse tissues and in human immune cells

Abstract: Background Lipid emulsions are a key component of total parenteral nutrition (TPN) and are administered to patients who are unable to ingest their daily required calories orally. Lipid emulsions rich with n–6 (ω-6) PUFAs are known to cause parenteral nutrition–associated liver disease and have inflammatory side effects, whereas n–3 PUFA-rich emulsions have favourable clinical outcomes. Objectives The present study used target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
0
10
0
3
Order By: Relevance
“…Thus, compared with mice given soybean oil, PN with fish oil resulted in significantly increased EPA‐ and DHA‐derived SPMs such as maresins 1 and 2, protectin D1, protectin DX, and resolvin D5, and decreased inflammatory lipid mediators such as LTB4 and PGD2 69 . A further study investigating these aspects in the murine model of PN found that fish oil shifts the lipid mediator profile towards omega‐3 PUFA‐based lipid mediators in the liver and that SPMs (including resolvin D1, maresin 1 and 2, and protectin D1 and DX), were higher in the livers of mice given fish oil compared with those given soybean oil 70 . Moreover, the murine spleen was identified as a rich source of lipid mediators and SPM formation, as lipid mediator concentrations were approximately 25‐fold higher in the spleen than in the liver 70 .…”
Section: Introductionmentioning
confidence: 95%
“…Thus, compared with mice given soybean oil, PN with fish oil resulted in significantly increased EPA‐ and DHA‐derived SPMs such as maresins 1 and 2, protectin D1, protectin DX, and resolvin D5, and decreased inflammatory lipid mediators such as LTB4 and PGD2 69 . A further study investigating these aspects in the murine model of PN found that fish oil shifts the lipid mediator profile towards omega‐3 PUFA‐based lipid mediators in the liver and that SPMs (including resolvin D1, maresin 1 and 2, and protectin D1 and DX), were higher in the livers of mice given fish oil compared with those given soybean oil 70 . Moreover, the murine spleen was identified as a rich source of lipid mediators and SPM formation, as lipid mediator concentrations were approximately 25‐fold higher in the spleen than in the liver 70 .…”
Section: Introductionmentioning
confidence: 95%
“…In addition, studies depleting Kupffer cells suggest a role of Kupffer cells in 12- and 15-LOX regulated LT productions in the liver ( Dragomir et al, 2011 ). When exposed to apoptotic cells, liver macrophages are also shown to express 15-LOX and produce immunosuppressive HETEs and HDEAs ( Snodgrass et al, 2021 ), though spleen and bone marrow derived macrophages may be the major sources of the pro-resolving SPMs rather than Kupffer cells ( Noureddine et al, 2022 ). As the bioactive lipids are important mediators for inflammatory functions, the amount and species produced by macrophages under specific disease conditions dictates the specific inflammatory responses.…”
Section: Oxylipin and Functions In Liver Macrophagesmentioning
confidence: 99%
“…Sein Team detektierte SPM-Konzentrationen von um die 0,2 pg pro mg Milzgewebe, "und da haben wir deutliche Peaks gesehen." 8) Dieter Steinhilber bleibt skeptisch: "Ich habe meine Zweifel, dass solche subnanomolaren Konzentrationen signifikante biologische Effekte auslösen und denen der pro-inflammatorischen Lipidmediatoren entgegenwirken können, die in 100-bis 1000-fach höheren Konzen…”
Section: Trugschlussunclassified